2012
DOI: 10.3390/medicina48050033
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Thyroid Axis Hormones in Psychotic Patients on Hospital Admission: the Effects of Prior Drug Use

Abstract: The aim of this study was to determine the concentrations of thyroid axis hormones in psychotic patients on hospital admission and to search for the associations between the concentrations of these hormones and prior drug use as well as mental symptoms. Material and Methods. Psychiatric diagnoses, psychotropic drug use, and the severity of psychoses were evaluated using the standard methods on admission. Venous blood from patients and healthy controls was drawn for the analysis of free thyroxin (FT4), free tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Elevated serum thyroxine (T4) concentrations with or without decrease in triiodothyronine (T3) concentrations have been found in acute schizophrenic patients [ 7 ] as well as in patients with other severe mental disorders, such as acute major depression and mania [ 8 - 10 ]. In our recent cross-sectional study [ 11 ], we have confirmed that patients with acute psychosis upon admission to the hospital had elevated T4 concentrations, especially patients who were free from treatment with antipsychotics. This syndrome of elevated T4 concentrations in acutely psychotic patients is coined as transient hyperthyroxinemia because it usually resolves during recovery from a psychotic episode [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 57%
“…Elevated serum thyroxine (T4) concentrations with or without decrease in triiodothyronine (T3) concentrations have been found in acute schizophrenic patients [ 7 ] as well as in patients with other severe mental disorders, such as acute major depression and mania [ 8 - 10 ]. In our recent cross-sectional study [ 11 ], we have confirmed that patients with acute psychosis upon admission to the hospital had elevated T4 concentrations, especially patients who were free from treatment with antipsychotics. This syndrome of elevated T4 concentrations in acutely psychotic patients is coined as transient hyperthyroxinemia because it usually resolves during recovery from a psychotic episode [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 57%
“…Elevated serum SHBG as a marker of tissue effects of thyroid hormones was also observed. These changes were also found after excluding patients with autoimmune thyroid disease or prior thyroid dysfunction and untreated with antipsychotics (Steiblien_ e et al 2012). In most instances, the thyroid status normalized within 2 weeks, and no treatment directed at thyroid gland was indicated.…”
Section: Other Nonstructural Hpt Axis Dysfunctionsmentioning
confidence: 83%
“…In most instances, the thyroid status normalized within 2 weeks, and no treatment directed at thyroid gland was indicated. Possible explanations for this phenomenon included disturbed T4 uptake or metabolism in the central nervous system or centrally mediated TSH hypersecretion (Steiblien_ e et al 2012). In some instances, a high T4 stage is viewed as an initial stage of NTIS due to acute inhibition of D1 deiodinase or increase in TBG levels often in elderly or psychiatric patients, but progressing further to low T4 stage of NTIS (Lee and Farwell 2016).…”
Section: Other Nonstructural Hpt Axis Dysfunctionsmentioning
confidence: 99%
“…These mechanisms motivated us to explore the differential effects of the mood groups on TH secretion levels (T3 and T4 cells), which are sensitive to stress and social environment and also affect lymphocyte (NK, T and B) cell count [17, 28]. We particularly expect the relation between TH secretion levels and lymphocyte cell count to occur in the anhedonic group because hyposecretion of T3 and T4 leads to hypothyroidism and depression [30, 31]. Hypothyroidism is known to be related to lower NK cell count, which is a sign of immune system malfunctioning in people suffering from anhedonia [31].…”
Section: Theorymentioning
confidence: 99%
“…We particularly expect the relation between TH secretion levels and lymphocyte cell count to occur in the anhedonic group because hyposecretion of T3 and T4 leads to hypothyroidism and depression [30, 31]. Hypothyroidism is known to be related to lower NK cell count, which is a sign of immune system malfunctioning in people suffering from anhedonia [31]. In contrast, people who suffer from hyperthyroidism experience mood swings; hence we expect to see T3 and T4 hypersecretion in the hedonic group [31].…”
Section: Theorymentioning
confidence: 99%